Nurse students' perception of the academic learning environment in Tunisian institutes of nursing sciences: A multisite cross-sectional study. (April 2022) - Boukhris, Khouloud; Zedini, Chekib; El Ghardallou, Mariem
Abstract: Background: A learning environment is an important determinant of students' learning behaviours, professional competencies, and academic performances. It is also an essential indicator of the quality of teaching programmes. To date, there is not a Tunisian study, that analysed nurse students' perceptions of the educational environment. Aims: This study aimed to assess the perception of Tunisian higher nursing institutes students regarding the quality of the learning environment, and identify the factors associated with it. Design: Multi-site cross-sectional survey. Setting: Five universities of nursing sciences in Tunisia. Participants: Undergraduate nursing students (n = 736). Methods: A cross-sectional descriptive study was conducted during the academic year 2019–2020. The Dundee Ready Educational Environment Measure (DREEM) questionnaire was used to describe the students' perceptions of the learning environment. The participants were recruited using a convenience sampling method. Statistical analyses were performed using SPSS version 20. One-way analysis of variance and t -test were used to compare the DREEM scores and socio-demographic/academic characteristics. A p -value of less than 0.05 was considered significant. Results: The mean overall DREEM score was 110.92 ± 20.55, indicating a positive perception of the learning environment. The year of study was significantly associated with total DREEM scores, with first-year students scoring higher than third- and second-year students ( p  = 0.035). The perception of the learning environment varied significantly among the five institutes ( p  < 10 −3 ). Demotivated atmosphere, lack of a support system, poor timetable organisation, and teacher-centred learning were revealed as problematic areas that needed improvement (individual score < 2). Our adapted version of the DREEM obtained acceptable internal consistency (Cronbach's alpha coefficient of 0.881). Conclusions: The study reported positive perceptions of the students regarding their academic learning environment. However, the DREEM scores reflected a traditional learning environment. It is essential to re-engineer the curriculum and shift the teaching paradigm towards 'student-centred curriculum' to enhance both the effectiveness and the efficiency of the learning environment.